Recent Development in Merchant Banking in India: An Review: Understanding the Role of Merchant Banking in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The term merchant bank refers to a financial institution that invests in businesses inexchange for ownership stakes rather than interest payments. Merchant banks also provide their clientcompanies with advice on corporate issues. The phrase merchant bank has historical significance inBritain and refers to a financial institution there. Merchant banks may be thought of as financialadministrations firms that also engage in private value speculating and provide venture banking and othersubsidiary services. Since a merchant bank serves as a consultant, middleman, and leader, it takes alonger-term view than the typical investment bank and is more concerned with the viability of eachinvestment opportunity and the provision of sound advice to each client business. Commonly used torefer to Investment Banks, commercial banks have a long history in banking. In addition, it may be usedto characterize the banking industry's private value activities. From the Middle Ages forward, this articlefocuses on the background of banking as it was developed by merchants. A nation's economic growth isdirectly proportional to the strength of its business sector, which is why merchant banking is soimportant. Recent development in merchant banking in India.